Strategi Kepemimpinan Kepala Sekolah dalam Implementasi Manajemen Berbasis Sekolah di SDN 187/I Teratai - Nofeni Ramadani (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2026)
This study aims to describe the principal's leadership strategies in the implementation of School-Based Management (SBM) at SDN 187/I Teratai. The study employed a qualitative approach with a descriptive method. The research informants consisted of the principal and 12 teachers of SDN 187/I Teratai, selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings revealed that the principal implemented participative, democratic, and collaborative leadership strategies in the implementation of SBM. The participative strategy was reflected in the involvement of teachers and educational staff in school program planning. The democratic strategy was implemented through open communication and deliberation in decision-making processes. Meanwhile, the collaborative strategy was carried out by establishing effective cooperation with the school committee and parents. The implementation of SBM at SDN 187/I Teratai reflected the principles of participation, autonomy, transparency, and accountability. The findings indicate that the principal's leadership strategies play an important role in supporting the successful implementation of SBM, thereby creating effective school management and contributing to the improvement of educational quality.